La gimnasia cerebral para fortalecer el desarrollo cognitivo de los niños de educación inicial - Masaquiza Masaquiza, Mónica Elizabeth (2022)
The present investigation addressed as problematic the difficulties in the cognitive development of children in initial education, due to the health emergency that is still going through, the children were limited to certain activities by remaining static for a long time in front of an electronic device (computer, cell phone, etc.). ), without major movements and recreation, which are essential in children for new neural connections, which is why the established objective was to strengthen the cognitive development of children in initial education of the Educational Unit "La Gran Muralla" applying brain gymnastics . The methodology used has a mixed qualitative-quantitative approach, with the field modality, bibliographic, using the deductive method. The focus group techniques were applied to the authority and teachers, a survey of parents and observation of children in initial education, with the data obtained, the shortcomings in cognitive development were evidenced, which led to the design of the guide proposal of Brain gymnastics to strengthen the cognitive development of children in initial education, which has fourteen innovative and complementary activities according to the age of the children, which after being applied, the results showed that when performing the brain exercises, the brain prepares, goes developing cognitive skills such as perception, attention, concentration, memory and language, giving way to the acquisition of skills, this is evidenced by the analysis of the pre-test and post-test, where progress was found in children of initial education . In addition, the proposal was validated by experts and users considering it to have a national impact since it can also be applied in other educational institutions.